Analysis of The Implementation of Transit Oriented Development (TOD) Policies to Optimize the Integration of Public Transportation Modes - Oktafianus, Cokky; Fachrial, Peppy; Kania, Dinar Dewi (Dinasti Publisher, 2024)
Efforts to reduce congestion in Jakarta are by providing Transit-Oriented Areas (KBT) connected to several other modes of public transportation, such as Kereta Cepat Indonesia (KCI), LRT, MRT, and Transjakarta. The central government's plan related to Transit-Oriented Areas, the DKI Provincial Government has issued Perda 1/2012 concerning the 2030 regional spatial plan in Chapter 1 Article 75